Validation of a cerebral hemodynamic model with personalized calibration in patients with aneurysmal subarachnoid hemorrhage - Shen, Yuanyuan; van der Harst, J. Joep; Wei, Yanji; Bokkers, Reinoud P. H.; van Dijk, J. Marc C.; Uyttenboogaart, Maarten (Frontiers in Bioengineering and Biotechnology, 2022)
This study aims to validate a numerical model developed for assessing personalized circle of Willis (CoW)-hemodynamics under pathological conditions. Based on 66 Computed Tomography Angiography (CTA) images, investigations were obtained from 43 acute aneurysmal subarachnoid hemorrhage (aSAH) patients administrated in local neurovascular center. Mean flow velocity of each artery in the CoW measured by Transcranial Doppler (TCD) and simulated by numerical model were obtained for comparison. The intraclass correlation coefficient (ICC) over all cerebral arteries of TCD and the numerical model was 0.88 (N=561; 95% CI 0.84-0.90). In a subgroup of patients who developed delayed cerebral ischemia (DCI), ICC decreased to 0.72, but remained constant with respect to changes in blood pressure, Fisher grade, and location of the ruptured aneurysm. Our numerical model showed a good agreement with TCD in assessing flow velocity in the CoW of patients with aSAH. In conclude, the proposed model can satisfactorily reproduce the cerebral hemodynamics under aSAH conditions by personalizing the numerical model with the TCD measurement. Trial registration number NL8114.